Filtered pulsed cathodic arc deposition of fullerene-like carbon and carbon nitride films - Tucker, Mark; Czigany, Z.; Broitman, E.; Naslund, L.; Hultman, L.; Rosen, J. (American Institute of Physics, 2014)
Carbon and carbon nitride films (CN x , 0 ≤ x ≤ 0.26) were deposited by filtered pulsed cathodic arc and were investigated using transmission electron microscopy and X-ray photoelectron spectroscopy. A “fullerene-like” (FL) structure of ordered graphitic planes, similar to that of magnetron sputtered FL-CN x films, was observed in films deposited at 175 °C and above, with N2 pressures of 0 and 0.5 mTorr. Higher substrate temperatures and significant nitrogen incorporation are required to produce similar FL structure by sputtering, which may, at least in part, be explained by the high ion charge states and ion energies characteristic of arc deposition. A gradual transition from majority sp3-hybridized films to sp2 films was observed with increasing substrate temperature. High elastic recovery, an attractive characteristic mechanical property of FL-CN x films, is evident in arc-deposited films both with and without nitrogen content, and both with and without FL structure.